MiR‐542‐3p prevents ovariectomy‐induced osteoporosis in rats via targeting SFRP1. Issue 9 (16th April 2018) - Zhang, Xiguang; Zhu, Yun; Zhang, Chuanlin; Liu, Jianping; Sun, Tianming; Li, Dan; Na, Qiang; Xian, Cory J.; Wang, Liping; Teng, Zhaowei
Abstract : Secreted frizzled‐related protein‐1 (SFRP1) is a negative regulatory molecule of the WNT signaling pathway and serves as a therapeutic target for bone formation in osteoporosis. In this study, we first established an ovariectomized (OVX) rat model to simulate postmenopausal osteoporosis and found significant changes in miR‐542‐3p and sFRP1 expression by RNA sequencing and qRT‐PCR. In addition, there was a significant negative correlation between miR‐542‐3p and sFRP1 mRNA levels in postmenopausal women with osteoporosis. We found that miR‐542‐3p inhibited the expression of sFRP1 mRNA by luciferase reporter assay. When the miR‐542‐3p binding site in sFRP1 3'UTR was deleted, it did not affect its expression. Western blot results showed that miR‐542‐3p inhibited the expression of SFRP1 protein. The expression of SFRP1 was significantly increased in osteoblast‐induced mesenchymal stem cells (MSC), whereas the expression of miR‐542‐3p was significantly decreased. And miR‐542‐3p transfected MSCs showed a significant increase in osteoblast‐specific marker expression, indicating that miR‐542‐3p is necessary for MSC differentiation. Inhibition of miR‐542‐3p reduced bone formation, confirmed miR‐542‐3p play a role in bone formation in vivo. In general, these data suggest that miR‐542‐3p play an important role in bone formation via inhibiting SFRP1 expression and inducing osteoblast differentiation. Abstract : sFRP1 and miR‐542‐3p were negatively correlated in postmenopausal osteoporosis patients. sFRP1 was a target of miR‐542‐3p. miR‐542‐3p play an important role in bone formation by targeting SFRP1 and inducing osteoblasts differentiation.